Enzalutamide or Abiraterone Acetate With Prednisone in the Treatment of Metastatic Castration-resistant Prostate Cancer in Real-life Clinical Practice: A Long-term Single Institution Experience - Fiala, Ondrej; Hosek, Petr; Korunkova, Hana; Hora, Milan; Kolar, Jiri; Windrichova, Jindra; Sorejs, Ondrej; Topolcan, Ondrej; Travnicek, Ivan; Sedlackova, Hana; Finek, Jindrich (Anticancer research, 2023)
BACKGROUND/AIM: Enzalutamide (ENZ) and abiraterone acetate with prednisone (AAP) represent novel hormonal therapies used in the treatment of metastatic castration-resistant prostate cancer (mCRPC). The aim of the study was to assess the long-term outcome of mCRPC patients treated with ENZ or AAP in real-life clinical practice. PATIENTS AND METHODS: The outcomes of 337 mCRPC patients treated with ENZ or AAP were retrospectively analysed. RESULTS: Median radiographic progression-free (rPFS) and overall survival (OS) of patients treated in the first line (pre-chemotherapy) was 13.89 (95% CI=12.40-16.80) and 31.02 (95% CI=24.27-37.44) months vs. 10.97 (95% CI=8.97-14.82) and 26.57 (95% CI=15.97-33.92) months for those treated in the second line (post-chemotherapy). We found inferior survival for patients with synchronous metastases, high Gleason score (GS) and visceral metastases. CONCLUSION: The efficacy of both ENZ and AAP in mCRPC patients is herein confirmed. Synchronous metastases, high GS and visceral metastases were identified as significant adverse prognostic factors.
Keywords: castration-resistant prostate cancer; retrospektivní studie; Humans; protokoly protinádorové kombinované chemoterapie; Prednisone; Antineoplastic Combined Chemotherapy Protocols; Enzalutamide; real-life practice; Nitriles; mužské pohlaví; prednison; metastatic; výsledek terapie; Abiraterone Acetate; Treatment Outcome; abiraterone acetate; nádory prostaty rezistentní na kastraci; nitrily; abirateron; lidé; Prostatic Neoplasms, Castration-Resistant; Male; Retrospective Studies